Cost–Performance Optimization of a Renewable Energy Resources Based Multimicrogrid System - Aljwary, Adel; Ziyodulla Yusupov; Muhammet Tahir Guneser (Journal of Advanced Industrial Technology and Application, 2024)
The objective of this paper is to optimize a multiobjective problem of a renewable energy resources (RER) based multimicrogid (MMG) system considering the output variation of the photovoltaic (PV) and wind Turbine (WT) as renewable energy resources and variation of the load demand and electricity prices. In this paper three microgrids (MGs) are connected with IEEE 33- bus distribution system each MG consists of a PV and WT. A three objective functions are modeled for this system to optimize the total annual cost, the voltage deviation and the voltage stability index (cost –performance multiobjective function). The optimization problem is solved with particle swarm optimization (PSO) technique for the system with and without RER. The results of the simulation show that the system is cost- performance optimized. A comparison is carried out with two other optimization techniques, mountain gazelle optimization (MGO) and gorilla troop optimization (GTO).